Transformasi Kejahatan Digital dan Tantangan Penegakan Hukum dalam Era Kecerdasan Buatan dan Big Data - Rizal Dwi Kurniawan; Bagas Pratama Wicaksono (Universitas Sains dan Teknologi Komputer, 2026)
The rapid advancement of Artificial Intelligence and big data technologies has significantly transformed the landscape of digital crime, increasing both its scale and complexity. This study aims to analyze the evolving patterns of cybercrime and examine the gap between technological advancement and institutional readiness in addressing these threats. A descriptive qualitative approach was employed using secondary data collected from global cybersecurity reports and relevant academic literature. The analysis was conducted through trend mapping and comparative interpretation to identify dominant crime types and their development patterns. The findings reveal that phishing remains the most prevalent form of cybercrime, accounting for approximately 38% of total incidents, followed by ransomware at 27% and data breaches at 21%. Meanwhile, AI-based fraud, although representing only 14%, exhibits the highest growth rate and complexity index, increasing by over 60% in recent years. The study also identifies a significant gap in law enforcement readiness, particularly in handling AI-driven crimes, which require advanced technical capabilities and longer investigation time. These results highlight that digital crime is evolving in a non-linear and exponential manner, driven by technological innovation and human vulnerability factors. The study contributes to the field of digital criminology by integrating crime trend analysis with institutional capacity perspectives. It emphasizes the need for adaptive policies, technological integration in law enforcement, and a multidisciplinary approach to effectively combat emerging cyber threats.